Digital Marketing in Developing Brand Awareness of MSMEs - Zaini Abdul Malik; Popon Srisusilawati; Irma Yunita Silviany; Risma Mustika Fajaria; Shakila Carisya Tsania (School of Business, IPB University (SB-IPB), 2022)
This large-scale social restriction by the government has a major impact on all activities. This has a big impact on MSMEs. In the MSMEs aspect, the COVID-19 pandemic has caused a decline in performance from the demand side (consumption and purchasing power of the people) which ultimately has an impact on the supply side, namely termination of employment and the threat of credit financing jams, even some MSMEs are not operating. The purpose of this research is to analyze digital marketing in building brand awareness used by MSMEs during the pandemic. Research method this is qualitative research with use studies case. Data study get through observation and interview, as well as supported by documentation researcher. Results study showing that digital marketing in build brand awareness done through Facebook social media management with do activity in the form of advertisement as well as operate technique mix marketing as personal selling, sales promotion and public relations as effort build brand awareness MSMEs products in particular street vendors around Unisba. Keywords: brand awareness, digital marketing, MSMEs, Unisba row stalls